Strategic Oversight Effectiveness of the Board of Commissioners: Prioritizing Critical Business Challenges and Designing a Monitoring System at PT Pertamina Hulu Energi - Ferry Firmansyah; Santi Novani (Green Publisher, 2026)
PT Pertamina Hulu Energi (PHE), Pertamina's Upstream Subholding, is facing strategic challenges owing to operations, commodity price volatility, and financial concerns. These circumstances compel that the Board of Commissioners concentrates its oversight on the most important business concerns affecting the company's profitability. This research analyzes and prioritizes PHE's important business concerns, as well as designing a targeted supervision framework. A sequential exploratory mixed-methods approach was employed, incorporating corporate document inspection, fourteen semi-structured interviews, thematic coding, and Best-Worst Method prioritizing with twelve respondents. The research discovered fifteen business issues and seven faults in the present oversight method. Impact appears to be the major factor, followed by urgency and probability. Four challenges were classified as Tier 1 priorities: mature field natural decline, asset integrity and unplanned shutdowns, post-investment review gap, and governance and Business Judgment Rule risk. The findings were translated into a Tiered BoC Oversight System consisting of a tiered work plan, monitoring toolkit, escalation and contingency protocol, enabling conditions, and integration with PHE’s existing BoC Oversight system namely SRAM, PRAM, and GOC architecture. The system sharpens, rather than replaces, the existing oversight architecture.